What are the risks with corticosteroid injections for plantar fasciitis?. Issue 2 (February 2018) - Hawks, Matthew; Larouche, Joseph
Abstract : EVIDENCE‐BASED ANSWER : Pain with injection is the most common reported adverse event from corticosteroid injections for plantar fasciitis, with 13% to 100% of study patients reporting pain (SOR: B, systematic reviews of RCTs with incomplete reporting). Corticosteroid injections are associated with plantar fascia rupture in 2.4% of patients after a mean of 2.7 injections (SOR: B, retrospective cohort study).